After the flood: Speculative architecture in a post-climate crisis world - Tóth, Aletta Zsuzsanna (My University, 2025)
“Climate change is not a crisis of technology—it is a crisis of the imagination.” Addressing climate change requires more than technological advancements; it demands creative, systemic thinking and the ability to envision alternative futures. This master’s thesis explores how speculative fiction can inspire architects to conceptualize new ways of living and dwelling. Through the lens of speculative architecture, it aims to contribute to a discourse that serves as a catalyst for making alternative futures possible. The thesis investigates how climate fiction, media tools, and narrative storytelling can act as platforms for site-specific speculative visions. It focuses on coastal residential buildings in Gothenburg, Sweden, imagining their future under a global warming scenario exceeding 4°C, as projected by the IPCC under the current emissions trajectory. The study examines four major climate hazards associated with this scenario and their impact on the built environment at both macro and micro scales. To explore responses to these extreme conditions, the thesis considers how speculative architectural scenarios might be presented in ways that shape public imagination toward coexistence with rising sea levels, rather than reinforcing narratives of retreat or defense. By reframing adaptation as an opportunity for flourishing, it seeks to highlight design approaches that move beyond survival toward thriving in altered environments. The primary focus is on flooding and extreme rainfall events, analyzing their implications for urban infrastructure and daily life. The thesis culminates in the design of a speculative street section along the Göta River, conceptualized as an abstraction of a typical Gothenburg street. Through first-person narrative storytelling, it showcases possible architectural and urban adaptations to these climate challenges, offering an immersive perspective on future life in a waterlogged city.
Keywords: speculative design; climate fiction; flooding; environmental futures